2004
DOI: 10.1038/sj.bjc.6602141
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TGF-β by infiltrated granulocytes correlates with the expression of collagen mRNA in pancreatic cancer

Abstract: Pancreatic cancer is often associated with an intense production of interstitial collagens, known as the desmoplastic reaction. To understand more about desmoplasia in pancreatic cancer, the expression of mRNA for type I and III collagens and potent desmoplastic inducing growth factors transforming growth factor-b (TGF-b), connective tissue growth factor (CTGF), acidic and basic fibroblast growth factor (FGF), platelet-derived growth factor (PDGF) A and C and epidermal growth factor (EGF) was analysed by quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 42 publications
1
53
0
1
Order By: Relevance
“…8,9 Neutrophils are the major producers of a number of ligands that may induce tumour cell proliferation and invasion, including transforming growth factor-. 43 Furthermore, granulocytes, particularly neutrophils, contain over two-thirds of circulating vascular endothelial growth factor, liberation of which may promote tumour vascularisation. 44 Neutrophils may further promote invasion and metastasis through the production and release of matrix metalloproteinases 45 and the promotion of cancer cell intra-and extravasation.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Neutrophils are the major producers of a number of ligands that may induce tumour cell proliferation and invasion, including transforming growth factor-. 43 Furthermore, granulocytes, particularly neutrophils, contain over two-thirds of circulating vascular endothelial growth factor, liberation of which may promote tumour vascularisation. 44 Neutrophils may further promote invasion and metastasis through the production and release of matrix metalloproteinases 45 and the promotion of cancer cell intra-and extravasation.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiling of tumor-stromal interactions between pancreatic cancer cells and stromal fibroblasts showed that multiple genes are differentially expressed in pancreatic cancer cells and in fibroblasts as a consequence of their mutual interactions (23). Desmoplastic reaction, a very prominent feature of PDACs in vivo (3), is composed of mainly type I collagen deposited by fibroblasts (12), and the extracellular matrix in the desmoplastic reaction has also been shown to modulate the behavior of pancreatic cancer cells (33,35). In this report, we show that the extracellular matrix deposited by pancreatic fibroblasts and cancer cells modulates the behavior of pancreatic ductal cells by inducing a more scattered phenotype and enhancing cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in human surgical specimens, there is a strong correlation between expression of TGF-h1 mRNA and type I collagen mRNA, suggesting that TGF-h1 may directly be responsible for the fibrotic reaction in PDAC tumors (12). TGF-h1 signals through cell surface serinethreonine kinases to activate cellular responses (13).…”
Section: Introductionmentioning
confidence: 99%
“…The PCR primer pair used for FGF-2 was described previously. 28 Results were obtained as an average of measurements performed in triplicate.…”
Section: Real Time Reverse Transcription-pcrmentioning
confidence: 99%